Gone Missing - James Woodall (European Journal of Life Writing, 2024)
This memoir describes an act of biography-making, in this case of the Argentine writer Jorge Luis Borges. James Woodall revisits a period in his mid-thirties when he embarked on the first biography of Borges in English, commissioned in London, after the latter had died in 1986. In the context of revising, if not entirely renovating, the book as published in 1996, Woodall – now in his sixties – traces steps back to himself as he was then, and brings the whole writing and autobiographical processes up to date: to 2024.